PWE-330 Causes for delay in commencing adjuvant chemotherapy in rectal cancer. (22nd June 2015) - Jones, HG; Coyne, P; Evans, M; Davies, M; Khot, U; Chandrasekaran, T; Hatcher, O; Gwynne, S; Beynon, J; Harris, D
Abstract : Introduction: Adjuvant chemotherapy is routinely recommended for locally advanced colorectal cancer (CRC). Recent guidelines state that adjuvant chemotherapy should be considered for patients with high-risk stage II and all stage III rectal cancer to reduce the risk of local and systemic recurrence (NICE 2014). It is recommended that adjuvant chemotherapy is scheduled to begin within 6 weeks of surgery, as delay has been shown to reduce overall survival (OS) and disease free survival (DFS). 1 Method: All patients having rectal cancer surgery in a single tertiary centre with curative intent in 2012/13 were included. Patients were excluded if the post-operative MDT decision did not include adjuvant chemotherapy. Data was gathered on patient demographics, staging, length of stay, type of surgery, date of MDT decision and date of commencement of adjuvant chemotherapy. Data on postoperative morbidity (Clavien Dindo Scoring) and mortality was obtained through the patients' notes, and the Index of Multiple Deprivation (IMD) was calculated using the patient's postcode. Statistical testing using ANOVA and Pearson's correlation coefficient were used to determine any risk factors for a delay in starting therapy. Results: There were 102 patients identified having surgery for rectal cancer in 2012/13. Of these, the MDT decision was for 46 to proceed with adjuvant chemotherapy. The median age was 63 (52–73), with a 2:1 male predominance. The median length of stay was 11 days (IQR 8–17 days), with 50% having non-restorative surgery. The median duration from surgery to commencement of adjuvant chemotherapy was 59.5 days (IQR 50–85 days), with an OS of 755 days (IQR 602–923 days) and DFS of 673 days (IQR 240–912 days). ANOVA confirmed a link between the length of stay in hospital and the delay to commencement of adjuvant chemotherapy (p = 0.001). No other factors were statistically significant, although other factors such as the Clavien Dindo scoring and the IMD approached significance (p = 0.147 and 0.163 respectively).3 Conclusion: Delay in commencing adjuvant chemotherapy is known to be an adverse factor in OS and DFS. Being able to identify causes of these delays will help health professionals to understand and minimise the risk. This work has demonstrated that longer hospital inpatient stay during the time of the index operation lead to a significant delay in commencing adjuvant therapy. Further, large studies are needed to identify any reversible risk factors that could impact on patient outcomes. Disclosure of interest: None Declared. Reference: Biagi JJ, et al . Association between time to initiation of adjuvant chemotherapy and survival in colorectal cancer: a systematic review and meta-analysis. JAMA 2011;305(22):2335–42